Comparative Transcriptome Analysis between Broccoli (Brassica oleracea var. italica) and Wild Cabbage (Brassica macrocarpa Guss.) in Response to Plasmodiophora brassicae during Different Infection Stages - Zhang, Xiaoli; Liu, Yumei; Fang, Zhiyuan; Li, Zhansheng; Yang, Limei; Zhuang, Mu; Zhang, Yangyong; Lv, Honghao (Frontiers in Plant Science, 2016)
Clubroot, one of the most devastating diseases to the Brassicaceae family, is caused by the obligate biotrophic pathogen Plasmodiophora brassicae. However, studies of the molecular basis of disease resistance are still poor especially in quantitative resistance. In the present paper, two previously identified genotypes, a clubroot-resistant genotype (wild cabbage, B2013) and a clubroot-susceptible genotype (broccoli, 90196) were inoculated by P. brassicae for 0 (T0), 7 (T7) and 14 (T14) day after inoculation (DAI). Gene expression pattern analysis suggested that response changes in transcript level of two genotypes under P. brassicae infection were mainly activated at the primary stage (T7). Based on the results of DEGs functional enrichments from two infection stages, genes associated with cell wall biosynthesis, glucosinolate biosynthesis and plant hormone signal transduction showed down-regulated at T14 compared to T7, indicating that defense responses to P. brassicae were induced earlier, and related pathways were repressed at T14. In addition, the genes related to NBS-LRR proteins, SA signal transduction, cell wall and phytoalexins biosynthesis, chitinase , Ca2+ signals and RBOH proteins were mainly up-regulated in B2013 by comparing those of 90196, indicating the pathways of response defense to clubroot were activated in the resistant genotype. This is the first report about comparative transcriptome analysis for broccoli and its wild relative during the different stages of P. brassicae infection and the results should be useful for molecular assisted screening and breeding of clubroot-resistant genotypes.